Community Perceptions and Adaptation Strategies Toward Floods in Pedurenan Village, Tangerang City - Iman Tresnadi; Muhammad Sani Roychansyah (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH))
In Indonesia, many cities located along riverbanks are prone to flood disasters. This study seeks to know the people’s perceptions of flood and their strategies to cope with floods in the study area. This study was conducted as a field survey in Tangerang city, a suburban area of Greater Jakarta. A qualitative design using a case study approach was used in this research. The study reveals that floods in a suburban area like Tangerang city can be caused by both natural and human factors. The key findings can be summarized as follows. First, people employ some local-level measures to cope with floods, especially as an effort to minimize the impact. Second, as part of flood management in Tangerang city, integrated flood management should be considered. To maintain sustainable development in a suburban area, it will be crucial to create close public and local community relationships through the strengthening of coordination and social capabilities.